2021
DOI: 10.3390/biom11121836
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Beyond: Actors in Cancer

Abstract: Leptin is a 16-kDa multifunctional, neuroendocrine peptide hormone secreted by adipocytes in proportion to total adipose tissue mass, known to control food intake, energy homeostasis, immune response, and reproductive processes [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several interventions to block the development of cachexia would invigorate antitumor immune functions [ 50 , 51 ]. On the other hand, leptin, an adipocyte-derived hormone increased in proportion to total adipose tissue mass, has been shown to involve in both innate and adaptive immune responses [ 52 ]. Recent studies found that it might contribute to the enhancement of the host immune response activated by PD-1/PD-L1 inhibitors in cancer patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several interventions to block the development of cachexia would invigorate antitumor immune functions [ 50 , 51 ]. On the other hand, leptin, an adipocyte-derived hormone increased in proportion to total adipose tissue mass, has been shown to involve in both innate and adaptive immune responses [ 52 ]. Recent studies found that it might contribute to the enhancement of the host immune response activated by PD-1/PD-L1 inhibitors in cancer patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its physiological role in the body, leptin affects cancer development. Recent studies report that elevated leptin levels correlate with an increased risk of certain malignancies, which mainly include renal cell carcinoma [ 101 ], intestinal cancer [ 102 ], pancreatic cancer [ 103 ], breast cancer [ 104 ] and gynecological cancers, including endometrial cancer [ 105 ] and ovarian cancer [ 106 ]. The potential role of leptin in carcinogenesis is shown in Figure 2 .…”
Section: Leptinmentioning
confidence: 99%
“…Leptin can bind to its receptor (ObR), leading to a leptin/ObR axis involved in hallmark cancer features such as cellular survival, metabolism, angiogenesis, and metastasis. Leptin can also interact with other pathways such as sex hormones, such as oestrogen, and induce inflammation via cytokine production, for example, IL-6, which can lead to further stimulation of cellular signal transduction pathways (Barone and Giordano. 2021).…”
Section: Diet As a Risk Factor For Cancermentioning
confidence: 99%